A reagent-free, fouling-resistant electrochemical multifunctional peptide sensor for highly sensitive and rapid detection of Alzheimer's disease biomarkers - Yajing Ji; Xueqin Li; Xiumin Li; Xiaochun Hu; Wei Cong; Honggang Hu; Siyao Liu; Yan Chen (Materials Today Bio)
β-amyloid (Aβ) aggregates are critical biomarkers for the early diagnosis of Alzheimer's disease (AD). Numerous studies have shown that blood-based detection of Aβ aggregates can achieve similar or higher diagnostic accuracy than clinical cerebrospinal fluid tests. In this study, a reagent-free, anti-fouling electrochemical sensor based on a peptide aptamer was developed. This sensor exhibited anti-fouling and specific recognition capabilities, enabling highly sensitive and selective quantitative detection of Aβ aggregates in blood. The multifunctional peptide (MF-peptide) incorporated a hydrophilic sequence of alternating lysine (K) and glutamic acid (E) residues into the Aβ recognition peptide. The MF-peptide sensor was fabricated via the self-assembly of the MF-peptide onto a working electrode modified with gold nanoparticles. Experimental results revealed that the sensor exhibited excellent sensitivity to Aβ aggregates, with a strong bilinear response over a range of 0.3 fM–0.5 pM and a detection limit of 0.1 fM. The entire detection process was completed within 25 min. Moreover, the sensor displayed strong resistance to high concentrations of endogenous interferents (interference coefficient <12.76 %) and excellent selectivity in the presence of both interferents and Aβ aggregates. Additionally, the sensor was successfully used to accurately detect Aβ aggregates in human serum, maintaining its excellent bilinear response. This study presents a novel, efficient, and rapid strategy for detecting Aβ aggregates in human serum without complex pre-processing and provides practical support for the early clinical diagnosis of AD.